PERAN SUTRADARA DALAM FILM DOKUMENTER 'JERAT DILEMA: KONFLIK PEREMPUAN BERPERAN GANDA - Aurel Navira Ismail (2023)
The aim of this final project in the form of a documentary film is to raise a phenomenon, which often occurs in society but is often ignored, regarding the dual role of women. The documentary film "Jerat Dilema: Konflik Perempuan Berperan Ganta" focuses on the true stories of three mothers who have to live with their dual roles since they have no choice in their lives. In addition, the psychological and physical impact of the pressures and burdens they carry alone makes this film convey the message of women supporting women to further educate various levels of society and public awareness. The main role of the writer as a director during the process of making this documentary film has the final result of representing phenomena and reality through the three main characters, Sri, Iis, and Peni, in this film. Furthermore, the author used an expository style with a narrative approach and the delivery of a three-act structure to communicate the expected message. In addition, this documentary film which was considered a biographical genre, provided direct narratives from the main character, expert characters, and society, to research data in order to add knowledge and increase the audience's sense of awareness regards to the importance of the phenomenon being raised. Through a series of pre-production, production and post-production processes for 9 months, this documentary film has successfully aired on Atrim Production's YouTube channel with quite a positive audience response. Furthermore, the conflict of dual roles of women and the way they deal with it is conveyed in the documentary film through the portrayal of the character's dilemmatic side through the director's treatment. Based on the reality found, the character should experience inner conflict from the double burden, work pressure, social environment, psychological and physical impacts, as well as the child's condition that must be faced alone. In addition, the absence of choices in the life of the characters leads them to the sincerity of living their lives as women who have had dual roles for tens of years until today.